The Impact of Attention on Social Functioning in Survivors of Pediatric Acute Lymphoblastic Leukemia and Brain Tumors - Moyer, Katherine H. (2012)
BACKGROUND: The cognitive late effects experienced by many survivors of pediatric acute lymphoblastic leukemia (ALL) and brain tumors are well-established. The most commonly reported deficit is difficulty with attention. Problems with social functioning have also been identified, but their relationship with cognitive functioning is not well understood. This multi-site, cross-sectional study aimed to examine the impact of attention on social functioning. PROCEDURE: 469 survivors of ALL and brain tumors (55% ALL; 57% male) completed study procedures, including parent- and teacher-report measures of attention (Conners’ Rating Scales, Revised) and parent-report of social functioning (Social Skills Rating System) as part of their screening evaluation for a large clinical trial. Survivors were 12.1 years of age and 4.9 years from the end of treatment at the time of study. RESULTS: Results revealed that survivors’ parent-reported attention problems were uniquely associated with their social functioning, relative to known demographic- and treatment-related risk factors. Teacher-reported attention problems, in contrast, were not, despite a significant correlation between the two. Deficits in intelligence and female gender were also significantly associated with poor social functioning. CONCLUSIONS: Attention problems uniquely impact difficulties with social functioning in survivors of pediatric cancer. Future studies will need to further examine the relationship between attention and social functioning in survivors, particularly when assessed by teacher report.